PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI SMP PADA KONSEP POLA INTERAKSI MAKHLUK HIDUP BERDASARKAN INVENTARISASI SERANGGA POLINATOR PADA BUNGA TANAMAN HOLTIKULTURA DI DESA PENYASAWAN KABUPATEN KAMPAR - Nursal ' '; Elya Febrita '; Listyawati ' ' (Program Studi Pendidikan Biologi, 2014)
This study aims to determine the insect pollinators species in horticulture cropsflowers at Penyasawan Village Kampar Regency and for designing learning media arethe relevant to the Interaction Patterns of Living Things concept. This research is adescriptive study was conducted from June to November 2013. The method in thisstudy used a survey method. Determining of the research location by purposivesampling, based on the types of gardens in the Penyasawan Village Kampar Regency.That are cucumber (Cucumis sativus), luffa (Luffa acutangula), peppers (Capsicumannuum), and eggplant (Solanum melongena). Biological parameters measured is theinsect pollinators species, and physical parameters measured are temperature,humidity and light intensity. Based on the results of this study, founded 12 species ofinsects pollinators include Xylocopa confusa, Xylocopa latipes, Amegilla.sp, Apiscerana, Trigona.sp, Ropalidia fasciata, Nomia punctata, Hylaeus.sp, Meghachile.sp,Syrphus.sp, Hypolimna Bolina, and Appias libythea. The results of the study in theform of videos and photo of specimens will be used as a learning source of biologysuch as learning media (interactive multimedia) to supported the Interaction Patternsof Living Beings concept on material living interactions in the junior high schoolclass VII.Keywords: Insect pollinator , horticulture crops, multimedia biology learning